Serum Cystatin C in Chronic Kidney Disease: A Case-Control Study - Sukanya Shetty; Janice DSa; Tirthal Rai; Srinidhi Rai; Roopa Bhandary (Avicenna Journal of Medical Biochemistry, 2021)
Background: Chronic kidney disease (CKD) is a major public health concern in recent years mainly due to its adverse clinical outcomes. It is most commonly attributed to diabetes mellitus (DM) and hypertension (HTN). Among the several novel biomarkers discovered to detect impaired renal function, serum cystatin C (SCysC) has gained importance.